The Effects of a Trace Amount of Manganese and the Homogenization on the Recrystallization of Al–7Mg–0.15Ti Alloys - Yang-Chun Chiu (Molecules, 2021)
The aim of this study is to explore the effects of Manganese addition and homogenization treatment on the microstructures and mechanical properties of the Al–7Mg–0.15Ti (B535.0) alloy. The optical microscopy, electrical conductivity measurements, transmission electron microscopy, scanning electron microscopy (SEM + EBSD), as well as Rockwell hardness and tensile tests, were exploited for this purpose. The main objectives are to refine the grain size, inhibit grain growth in the annealed state, and enhance the mechanical strength of the alloy. The results show that the addition of manganese to the Al–7Mg–0.15Ti alloys refined the as-cast and recrystallized grains of the alloys. During the homogenization process, Al4Mn high-temperature stable dispersoids were precipitated in the aluminum matrix. After annealing, the Al4Mn particles blocked the movement of grain boundaries during the growth of the recrystallized grains and inhibited grain growth. Consequently, the annealed alloys showed grain refinement and dispersion strengthening. The Al4Mn dispersoids of the alloys with manganese added were smaller and denser after a two-stage homogenization process compared to those that underwent a one-stage homogenization process. By contrast, for the alloys without the addition of manganese, the recrystallized grains showed normal growth after annealing, and different homogenization processes had no significantly different effects.